Poly(vinyl alcohol)-based Electrospun Nanofibers: Characterization and Phytase Immobilization - Kamaci, Umran Duru; Peksel, Aysegul (BIOINTERFACE RESEARCH APPLIED CHEMISTRY, 2022)
The aim of this study is to immobilization phytase obtained from cowpea seeds into nanofiber-based on poly(vinyl alcohol) (PVA) and to investigate kinetic properties, optimal pH, and temperature of free and immobilized phytase. The structural analysis and morphological properties of the nanofibers are carried out via SEM and XRD. The results indicated that enzyme stability, pH, and thermal stability are increased after immobilizing phytase into the nanofiber. The optimum pH and temperature of the free and immobilized phytase are found as pH 5.0 and 45-65 degrees C, respectively. These results indicated that the immobilized phytase could be a good candidate for agriculture, animal feed, food, and medical applications.
Keywords: phytase; cowpea seeds; biocatalyst; nanofiber; RELEASE; Chemistry